"Ask Google Assistant Where to Travel" Tourists' Interactive Experiences With Smart Speakers: An Assemblage Theory Approach. (April 2023) - Jiménez-Barreto, Jano; Rubio, Natalia; Mura, Paolo; Sthapit, Erose; Campo, Sara
The emergence of the Internet of Things (IoT) has the potential to reframe interactions among tourists, destinations, and service providers in multiple ways. Yet, there is scant empirical evidence on how individuals develop their relationships with IoT devices and how this technology can serve tourists in planning and deciding on particular destinations or services. Drawing on the assemblage theory, we investigated tourists' interactive experiences when planning trips with and without smart speakers. Methodologically, we employed an interactionist/performative approach that included three qualitative studies to examine tourists' information production, expressive roles, and information processing styles during interactions with smart speakers in the pre-visit stage. The analysis was driven by grounded theory and utilized computerized psycholinguistic techniques to enrich our research implications for theory, methodology, and tourism management.